Implementasi Nilai Kewirausahaan Siswa Sekolah Dasar Melalui Market Day Pada Era Industri 4.0 (Studi Kasus SDN Pepe Sedati dan MI Darul Hikam Waru) - Arifin, She Fira Azka; Ni’matur Rochmah; Nur Rizki Septiani (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
ABSTRACT This research was conducted to determine the implementation of the market day program, the stages of its implementation, and the achievement of entrepreneurial character values at SDN Pepe Sedati and MI Darul Hikam Waru. This type of research is a qualitative descriptive study using purposive sampling and snowball sampling techniques while data analysis techniques include data reduction, data display, verification or conclusion drawing stages. The subjects of this study were teachers and students at SDN Pepe Sedati and MI Darul Hikam Waru. Based on the results of data analysis, it shows that the implementation of the market day program in each school has a different concept depending on the uniqueness of the school which is influenced by the vision and mission, as well as the policies in the school. The implementation phase of market day activities includes planning, production, buying and selling, and evaluation/reflection. In addition, the implementation of market day is able to instill entrepreneurial character values such as self-confidence, independence, caring, hard work, cooperation, social communication, creative and innovative, openness and orientation to the future, cultured, tenacity, spirit of leadership and sportsmanship, and dare to take risks. Market day activities as a means of developing entrepreneurial skills are inseparable from cognitive processes or applying knowledge and character building (affective). Keyword: Entrepreneurship, Market Day, Industry 4.0 ABSTRAK Penelitian ini dilakukan untuk mengetahui pelaksanaan program market day, tahapan pelaksanaannya, dan ketercapaian nilai-nilai karakter kewirausahaan di SDN Pepe Sedati dan MI Darul Hikam Waru. Jenis penelitian ini penelitian deskriptif kualitatif menggunakan teknik sampling purposive sampling dan snowball sampling sedangkan teknik analisa data meliputi tahap data reduksi, data display, verification atau conclusion drawing. Subjek penelitian ini yaitu guru dan siswa di SDN Pepe Sedati dan MI Darul Hikam Waru. Berdasarkan hasil analisis data menunjukkan penerapan program market day di setiap sekolah memliki konsep yang berbeda bergantung pada kekhasan sekolah yang dipengaruhi visi-misi, maupun kebijakan di sekolah. Tahap pelaksanaan kegiatan marketday meliputi perencanaan, produksi, jual beli, dan evaluasi/refleksi. Selain itu, pelaksanaan market day mampu menanamkan nilai-nilai karakter kewirausahaan seperti percaya diri, kemandirian, kepedulian, kerja keras, kerja sama, komunikasi sosial, kreatif dan inovatif, keterbukaan dan orientasi ke masa depan, berbudaya, keuletan, berjiwa pemimpin dan sportif, dan berani mengambil resiko. Kegiatan market day sebagai sarana mengembangkan keterampilan (skill) berwirausaha yang tidak terlepas dari proses kognitif atau menerapkan pengetahuan dan pembentukan karakter (afektif).